Environmental management accounting: an empirical investigation of manufacturing companies in Malaysia - Dayana, Jalaludin; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (University of South Australia, 2010)
Environmental management practices and the implementation of environmental management systems (EMS) have spurred interest in the adoption of environmental management accounting (EMA). EMA integrates environmental information with economic information. Through EMA, the accounting systems will explicitly identify, generate, analyze and use financial and non-financial environmental related information. This paper offers a review of the literature regarding EMA adoption followed by a survey report. The study also explores the associations between EMA, environmental performance and economic performance. To test the proposed relationships, a survey questionnaire was administered to accountants and environmental managers of manufacturing companies in Malaysia. The results of correlation analyses support the hypothesized relationships.